GENETIC DIVERGENCE ANALYSIS IN HRDC RICE (Oryza sativa L.) HYBRIDS IN BANGLADESH (Bangladesh Journal of Plant Breeding and Genetics, 2016)
Genetic divergence of 48 IRRI developed F1 rice hybrids were studied through Mahalanobis D2 and principal component analysis for ten characters in Gazipur and Pabna district during dry season 2012-13. Among 48 genotypes, cluster analysis resulted in five clusters following Wards method. During dry season for both regions, cluster I incorporated the highest number of genotypes. Significant differences among the genotypes but non-significant differences among replications were noticed for most of the parameters under study. The inter-cluster distance was larger than intra-cluster distance suggesting wider diversity among the genotypes. In Gazipur, the maximum inter-cluster D2 value was recorded between cluster III and V (6.69) and the minimum between cluster II and IV (0.69). The intra-cluster distance was maximum in cluster IV (3.60) and minimum in cluster I (0.33). In Pabna, maximum inter-cluster distance was exhibited between cluster IV and II (16.43) but minimum between cluster II and III (3.98). Maximum intra-cluster distance (4.40) was recorded in cluster IV whereas minimum in cluster I (0.83). Based on positive value of vector 1 and vector 2, panicle number m-2, spikelet fertility (%) and 1000-grain wt. (g) had maximum contribution towards genetic divergence among the characters studied. Cluster means indicated considerable differences in the mean values of different parameters. The highest cluster means for panicle weight (g), spikelet fertility (%), 1000 grain wt. (g) and grain yield (kg ha-1) were derived from cluster IV. Therefore, more prominence should be given to the lines under cluster IV that having genetic potentiality to contribute better for yield maximization of hybrid rice.